Variasi Morfologis Udang Galah (Macrobrachium rosenbergii de Man, 1879) Hasil Inbreeding dan Outbreeding Populasi Probolinggo dan Mahakam - Nurul Suwartiningsih; T. Trijoko; Niken Satuti Nur Handayani (Universitas Gadjah Mada, 2017)
Indonesia has high biodiversity, one of them is the diversity of giant freshwater prawn (Macrobrachium rosenbergii de Man, 1879). The giant freshwater prawn was easy to reproduce and has high nutritional value. This study was conducted to determine the morphological variation of inbreed and outbreed of Probolinggo and Mahakam (Mama, Gogo, Goma, and Mago) populations that was developed in Unit Kerja Budidaya Air Payau Balai Budidaya Udang Galah (UKBAP BBUG) Samas as a basic for seed selection. Research of morphological variation carried out by observing 12 morphological characters, four meristic characters and 52 morphometric characters in four populations. Analysis of basic morphometric characters using a statistical program to determine the linear regression and the significance of parameters. Analysis of morphological characters using a statistical program to make dendrogram showing the similarity of four populations. The result of morphometry shows that the ratio of cephalothorax and abdomen of Mago and Goma is lower than Mama and Gogo. When viewed from the ratio of the carapace and rostrum length, Mago produces the longest rostrum. So, when only carapace length is compared to abdomen length, Mago showed the greatest value. Gogo has the highest ratio of cephalothorax and abdomen, while Mago has the highest ratio of carapace and abdomen among populations. Morphological data analysis showed that Gogo and Goma had reached 76% similarity, Goma and Mama have a similarity of 68% while Mago has 52% similarity with another three populations.